anonymous
  • anonymous
Use the table to calculate the average rate of change from t=1 to t=4. t= 0, 1, 2, 3,4 x(t)= 8, 7,5,1,2 I don't know how to make a table. HELP PLEASE.
Calculus1
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
schrodinger
  • schrodinger
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
anonymous
  • anonymous
Hi @izhangy, technically you have your table already, because it is nothing more than a list of one variable (t) versus another variable, here x(t). The rate of change is defined as (x(t+1)-x(t)) / (t+1 - t). Looks impressive but is nothing more than a fancy way of telling you that you need to subract to successive x-values and divide this by two successive t-values. Let's start with the t-part. As you can see, t neatly increases with '1' for each step, going from 0 to 1 to...etc to 4. Every step is therefore of size '1' and that makes life easy. Now the x(t)-part. Just start with the first one, 8. The next value is 7, so the difference is 8-7=-1. In our formula above, this means that x(1) - x(0) = 8 - 7 = -1. The rate of change for this step is then: -1 / 1 = -1. Let's do the second one as an example too. Now we evaluate t=1, so we need x(t+1)=x(2), x(t)=x(1) and this goes together with t=2 and t=1. Just fill out the formula and find as rate of change for the second step: ( x(2)-x(1) ) / 2-1 = 5-7/1 = -2. The rate of change has increased from -1 to -2 by stepping from t=0 to t=1. Can you do the rest ?
anonymous
  • anonymous
|dw:1377673503586:dw|

Looking for something else?

Not the answer you are looking for? Search for more explanations.